Study of Antibody-Dependent Reactions of Mast Cells In Vitro and in a Model of Severe Influenza Infection in Mice - Mamontov, Andrey; Losev, Igor; Korzhevskii, Dmitrii; Guselnikova, Valeriia; Polevshchikov, Alexander; Desheva, Yulia (Frontiers in Immunology, 2021)
We investigated the reaction of mouse peritoneal mast cells (MCs) in vitro after IgG-containing immune complex introduction using A/H5N1 and A/H1N1pdm09 influenza viruses as antigens. The sera of immune mice served as a source of IgG antibodies. The concentration of histamine in the supernatants was determined at 4 hours after incubation with antisera and virus. We compared the contribution of MCs to the pathogenesis of post-immunization influenza infection with A/H5N1 and A/H1N1 influenza viruses in mice. The mice were immunized parenterally with inactivated viruses, thechallenge was done using lethal doses of drift A/H5N1 and A/H1N1 influenza viruses on the 14th day after immunization. Simultaneously, half of the mice were injected intraperitoneally with a mixture of histamine receptor blockers (chloropyramine and quamatel). In in vitro experiments, the immune complex formed by A/H5N1 virus and antiserum caused a significant increase in the histamine release compared to immune serum or the virus alone. With regard to the A/H1N1 virus, such an increase was not significant. A/H1N1 immunization caused detectable HI response in mice at 12th day after immunization, in contrast to the A/H5N1 virus. After challenge of A/H5N1-immunized mice, administration of antihistamines increased the survival rate by up to 90%. When infecting the A/H1N1-immunized mice, 90% of the animals were already protected from lethal infection by day 14; the administration of histamine receptor blockers did not increase survival. Histological examination of the lungs has shown that toluidine blue staining allows to estimate the degree of MC degranulation. The possibility of in vitro activation of murine MCs by IgG-containing immune complexes has been shown. In a model of influenza infection, it was shown that the administration of histamine receptor blockers increased survival. When the protection was formed faster due to the earlier production of HI antibodies, the administration of histamine receptor blockers did not significantly affect the course of the infection. These data allow to propose that even if there are antibody-dependent MC reactions, they can be easily stopped by the administration of histamine receptor blockers.